KEBIJAKAN KESELAMATAN DAN KEAMANAN MARITIM DALAM MENUNJANG SISTEM TRANSPORTASI LAUT - Muh Kadarisman (Institut Transportasi dan Logistik Trisakti, 2017)
The research aimed to analyze maritime safety and security policy in supporting of marine transportation system. This study uses descriptive method, because the data collected in the form of words, images, and not the numbers. The data comes from interviews, field observations, focus group discussions, videotapes, photos, notes or memos, and other official documents. Data analysis with ethical and emic approach and triangulation process. Determination of Informant with purposive technique. Result of research: Sea transport in Indonesia not yet optimally developed, but has strong potency to be developed, considering its characteristic able to do mass transportation. Therefore, the safety and security system is a key factor to be considered and as a basis and benchmark for decision makers. The safety and security system of sea transportation in Indonesia has not run optimally, there are still many accidents both because of natural factors and human factors. Government policies in the maritime field, whether the fishery industry or the shipping industry have not been implemented consistently in accordance with applicable law. So far, the development of maritime potential has been hit by structural problems, and there is no national political awareness of the magnitude of the economic, fisheries and maritime potentials. Little is known about the potential content of Indonesia’s marine resources, thus opening the door for various research and development of biodiversity.